Formation of conceptual provisions of tourism marketing - Kopytsia, Andrii; Lepskyi, Roman; Pererva, P. G. (Полтавський державний аграрний університет, 2023)
Three components that form the standard of service of a tourist organization in the field of hospitality are considered: personnel management, as it is the main resource for growth and prosperity in the service sector; improving the sales and service process (for example, the amount of time a guest checks in at the hotel); organization of the environment (interior), which creates a certain mood in the consumer and contributes to the attraction of buyers.
Формування концептуальних положень туристичного маркетингу
Keywords: tourist organizations; world economy; marketing; partners; services